Approaches to depreciation of investment production - E. Bogomolova; A. Kozlovsky; N. Moiseenko (Вестник университета, 2016)
In article some key questions are considered, allowing to solve a problem of investment activity and management of expenses from two interconnected positions - depreciation of investment production and creation of additional conditions for interest of investors in long-term investments. The estimation of the developed investment situation is given, principal causes of decrease in investment activity are revealed. Some ways of decrease in expenses to investitsionno-building sphere of economy are offered.